Criminal Policy as a Basis for the Sustainable Development or Public Security - Vilks, Andrejs (European Journal of Sustainable Development, 2019)
Sustainable development of public security should be based on a balanced, rational and effective criminal justice policy. Criminal justice policies can be perceived, valued and also implemented as a set of scientific theories and concepts on the conceptual, strategic and tactical elements of preventing and combating crime and other anti-social phenomena. The fight against crime can be recognized as an element of the cultural environment. It is not possible to achieve the effective functioning of society and its legal system without relying on general human norms and values. The criminal justice approach reflects the common values of the society, which are directed to the interests primarily protected. Criminal justice policy is concerned with the detection of criminogenic processes, crime, their determinants and the effectiveness of measures to prevent and combat crime. Keywords: Crime, Criminal policy, societal development, public security